(untitled) (International journal of artificial intelligence, 2024)
This article cites auscultation of the lung, its axamicity, and lists the order in which auscultation of the lung is performed in this case. The methodology of this process and the sequence of execution are presented on the basis of the procedure on what skills students will acquire in the process of disembarkation to students. This was done on the basis of the basic law rules on how to perform this process in the work of a doctor to students. This greatly allows students to accurately diagnose lung diseases.